1973
DOI: 10.1159/000197310
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-Intestinal Cell Loss in Man

Abstract: The rate of deoxyribonucleic acid loss (DNA) from the epithelial surface of human stomach, small intestine, large intestine and skin measures the rate of cell loss. From the data it is apparent that 287 g of cells are lost every 24 h from the mucosa of the entire human gastrointestinal tract. Evidence is presented to show that in the steady-state this loss reflects the rate of production or turnover of surface epithelial cells. In atrophic gastritis, coeliac syndrome, exfoliative psoriasis and possibly ulcerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In patients with duodenal ulcer the proliferative activity in gastric mucosa was found to be low, both by measurements of the rate of gastric DNA loss (Boyes et al, 1971) and in autoradiographic studies (Hansen et al, 1975). On the contrary, simple atrophic gastritis is associated with increased rates of cell proliferation (Boyes et al, 1971;Croft and Cotton, 1973;Steenbeck and Wolff, 1971), and in a preliminary study we found a high cell production rate in the gastric mucosal remnant after antrectomy (unpublished data). These findings suggest that the development of mucosal hypotrophy and atrophic gastritis after antrectomy in man is not simply caused by a decreased rate of cell renewal.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with duodenal ulcer the proliferative activity in gastric mucosa was found to be low, both by measurements of the rate of gastric DNA loss (Boyes et al, 1971) and in autoradiographic studies (Hansen et al, 1975). On the contrary, simple atrophic gastritis is associated with increased rates of cell proliferation (Boyes et al, 1971;Croft and Cotton, 1973;Steenbeck and Wolff, 1971), and in a preliminary study we found a high cell production rate in the gastric mucosal remnant after antrectomy (unpublished data). These findings suggest that the development of mucosal hypotrophy and atrophic gastritis after antrectomy in man is not simply caused by a decreased rate of cell renewal.…”
Section: Discussionmentioning
confidence: 99%
“…Valuable knowledge of cell turnover in the stomach has been obtained by measuring the cell loss from human gastric mucosa by estimation of the DNA content in gastric washings (Boyes, Crean, and Watkinson, 1971;Croft and Cotton, 1973). How-ever, the DNA rate represents the rate of loss of cells from both the antral and fundic part of the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Coghill (1966 developed a method to measure the rate of gastric DNA loss, which they used to estimate gastric cell turnover in man. The procedure has been used by other investigators (Max and Menguy, 1970;Croft and Cotton, 1973;Desai, Venugopalan, and Antia, 1973), but an assumption for its use must be that the cell proliferation kinetics are similar in the antral and fundic mucosa. Considering the secretory and histological differences between the two types of gastric mucosa, a different growth pattern may be expected.…”
mentioning
confidence: 99%
“…The host organ is lined with a perpetually and rapidly renewing epithelium: Ϸ20-50 million cells are shed per minute in the small intestine and 2-5 million per minute in the colon (9,10). This epithelium is able to maintain marked regional differences in the differentiation programs of its component cell lineages as it undergoes continuous replacement.…”
Section: We Are Not Alonementioning
confidence: 99%